COVID 19 Patients /Southern of Iraq: Character and Dermatologic Manifestations - Ahmed Abdul Hussein Kawen; Ali Abid Saadoon (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: the spread of coronavirus diseases (COVID-19) in China and then around the world wherethe current study explores the link between skin manifestations and COVID-19. Methods: A cross sectionalstudy including all diagnosed cases of COVID-19 in Thi-Qar and Al-Muthana governorates, where startedby the diagnosis of the 1st case in Thi-Qar province, and ended with the 21th of April 2020, the cases weredistributed as 62 cases from Thi-Qar and 54 cases from Al-Muthana, information had been gathered fromCOVID -19 isolation unites in the two main hospitals of isolation, Al-Husain teaching Hospital and AlMuthana teaching hospital. Results: The result showed that there are 116 cases of SARS-COV2 infectionwas recorded in Thi-Qar and Al-Muthanna, the high percentage of infection was detects in the middle adult80(69%) in the age group over 60 years old. The distribution of infection according to the gender revealedsignificant differences where the males comprise (87.75%) of cases. The direct contact route of transmissionwas predominant among patients 101 (87.1%). Also, the highest percentage was live 110(94.8%). Accordingto the results there was a negative relationship between the two variables was detected, there is no correlation.So, there is no correlation in skin manifestations according to the system involvement among COVID-19infected cases with the pearson correlation (0.327). The results show non-statistical significance in skinmanifestation according to biography among only who had dermatological lesions at p value (0.248). Also,there are non-statistical significant in source of infection according to skin manifestation and no correlationbetween skin manifestations and death with corona virus. Conclusions: It can be concluded from the currentstudy that there is no close correlation between skin manifestations and COVID-19 infection, a very weakdirect relationship because some patients may not show any symptoms and these are considered negativesigns, meanwhile the unique skin lesion are zinc like deficiency( acrodematitis enteropathica )not reportedin any other areas.